Exploring wellbeing and agency among urban youth through photovoice. (August 2016) - Rose, Theda; Shdaimah, Corey; de Tablan, Dante; Sharpe, Tanya L.
Abstract: This study elicited adolescent perspectives of wellbeing and agency using photovoice, a method that employs co-creation of meaning and knowledge around pictorial images. Participants (n = 12) were Baltimore City high school students in the 9th–11th grades, and diverse in terms of gender and race. Participants used cameras to photograph images that expressed wellbeing and agency. They then discussed, in focus groups, how their pictures reflected those constructs and their relationship to decision-making and academic success. Students highlighted different facets of individual and community wellbeing, as well as where and how wellbeing is fostered in their family, school, and neighborhood environments. Respondents differentiated between good and bad agency. They noted the power of agency as the power to change things, and the obligation that such power carries for themselves and the adults around them. Woven through both domains was respondents' future orientation; many of their observations were derived from the perceived impact on their own and others' academic and life trajectories. This research contributes to the wellbeing and agency research literature by adding the perspectives of urban adolescent youth. Findings also inform the development of more participatory community school-based interventions to foster wellbeing and agency among adolescents. Highlights: Respondents identified activities and places that enhanced wellbeing. Respondents recognized their own and others' power to change things. Respondents believed that the ability and obligation to make change are interdependent. Participant actions were based on the impact on their future and the community. Adolescent interventions should include their perspectives on wellbeing and agency.